Summoning the spirits: possession and invocation in contemporary religion - Dawson, Andrew (Library of modern religion, 2011)
Charismatic visions and the role of mediums; possession ceremonies and ecstatic trance; the social contexts and practices of invocation: these are a number of the intriguing topics addressed by this comprehensive undergraduate textbook, the first of its kind to offer a thorough overview of the fascinating and multifaceted subject of spirit possession. The subject is now widely studied in a number of fields - including religion, sociology, anthropology and cultural studies - and for some time there has been a need for a book which offers a multicultural, multi-thematic treatment which can satis